Resistance Test of Matoa Leaf Extract (Pometia pinnata J.R & G.Forst) On Fungi Growth of Candida albicans In-vitro - Intan Rahma Putri; Mades Fifendy; Gustina Indriati (Jurnal Serambi Biologi, 2022)
Fungal infection is one of the most common infectious diseases in the world, including Indonesia. Candidiasis is a dangerous disease, it is proven that the cases of death caused by candidiasis are in the range of 30-40% every year. Candidiasis is an infectious disease caused by fungi of the genus Candida, of which about 70% are caused by the species Candida albicans. Antifungal resistance can become a serious problem in the future. P. pinnata leaves are known to contain secondary metabolites, namely saponins, flavonoids, alkaloids, terpenoids and tannins. The purpose of this study was to determine the inhibition of P. pinnata leaf extract on the growth of the fungus C. albicans. This research was conducted using a completely randomized design (CRD) method with 6 treatments and 3 repetitions. The treatments were control using 10% ketoconazole and P. pinnata leaf extract (30%, 40%, 50%, 60%, 70%). The data that has been obtained were analyzed using ANOVA with a confidence level of = 5% and further tested with DNMRT. The results showed that P. pinnata leaf extract was able to inhibit the growth of the fungus C. albicans at concentrations of 70%, 60%, 50%, 40%, and 30% with an average diameter of the inhibition zones 10,10 mm, 11,62 mm, 12,78 mm, 12,34 mm, 10,97 mm.